EFISIENSI BIAYA PRODUKSI PUPUK ORGANIK PADA UNIT PENGELOLA PUPUK ORGANIK (UPPO) TANI MANDIRI I B DI DESA LOMBOK KULON KECAMATAN WONOSARI KABUPATEN BONDOWOSO - Fiky Fitasari; Triana Dewi Hapsari; Ebban Bagus Kuntadi (Jurnal Agribisnis Indonesia, 2017)
Agroinput needs of farming activities, especially fertilizer in Lombok Kulon village is supplied by UPPO Tani Mandiri I B in the village. Livestock population in Lombok Kulon village in 2012-2015 shows an increase of cattle population. The increase of livestock population will increase availability of raw materials for organic fertilizer, so it needs a good raw materials procurement system in the procurement process of livestock manure as raw materials for organic fertilizer. Therefore, the researcher wanted to analyze the production system on UPPO in Lombok Kulon village. The review of the organic fertilizer system production on UPPO in Lombok Kulon village besides viewing the technical aspect, but also can be viewed from the aspect of cost production to see whether the production activities of organic fertilizer is efficient. The results show that: (1) Procurement of livestock manure as raw materials for organic fertilizer on UPPO Tani Mandiri I B has fulfilled aspects of the raw materials procurement, ie quantity, quality, time, cost, and organization systems. (2) The production system of organic fertilizer viewed from three aspects, namely: production type of UPPO Tani Mandiri I B is a mix, facility layout of UPPO Tani Mandiri I B is a product layout. The processing of organic fertilizer on UPPO Tani Mandiri I B is less than in SOP. (3) The use of production costs on UPPO Tani Mandiri I B is efficient. The eficiency value of production costs is 1,84.